Refractory Hypertension. Issue 1 (July 2015) - Dudenbostel, Tanja; Acelajado, Maria C.; Pisoni, Roberto; Li, Peng; Oparil, Suzanne; Calhoun, David A.
<x xml:space="preserve">Abstract</x> Refractory hypertension is an extreme phenotype of treatment failure defined as uncontrolled blood pressure in spite of ≥5 classes of antihypertensive agents, including chlorthalidone and a mineralocorticoid receptor antagonist. A prospective evaluation of possible mechanisms of refractory hypertension has not been done. The goal of this study was to test for evidence of heightened sympathetic tone as indicated by 24-hour urinary normetanephrine levels, clinic and ambulatory heart rate (HR), HR variability, arterial stiffness as indexed by pulse wave velocity, and systemic vascular resistance compared with patients with controlled resistant hypertension. Forty-four consecutive patients, 15 with refractory and 29 with controlled resistant hypertension, were evaluated prospectively. Refractory hypertensive patients were younger (48±13.3 versus 56.5±14.1 years; P=0.038) and more likely women (80.0 versus 51.9%; P=0.047) compared with patients with controlled resistant hypertension. They also had higher urinary normetanephrine levels (464.4±250.2 versus 309.8±147.6 µg per 24 hours; P=0.03), higher clinic HR (77.8±7.7 versus 68.8±7.6 bpm; P=0.001) and 24-hour ambulatory HR (77.8±7.7 versus 68.8±7.6; P=0.0018), higher pulse wave velocity (11.8±2.2 versus 9.4±1.5 m/s; P=0.009), reduced HR variability (4.48 versus 6.11; P=0.03), and higher systemic vascular resistance (3795±1753 versus 2382±349 dyne·s·cm5·m2; P=0.008). These findings are consistent with heightened sympathetic tone being a major contributor to antihypertensive treatment failure and highlight the need for effective sympatholytic therapies in patients with refractory hypertension.